Public Regulation and Operating Conventions Affecting Sources of Funds of Commercial Banks and Thrift Institutions - Kreps, Clifton H.; Lapkin, David T. (Journal of Finance, 1962)
Clifton H. Kreps, Jr., David T. Lapkin, Public Regulation and Operating Conventions Affecting Sources of Funds of Commercial Banks and Thrift Institutions, The Journal of Finance, Vol. 17, No. 2 (May, 1962), pp. 289-301